Effect of academic stress on physical activity level and cognitive functions in first year medical students: An observational study - Sorout, Jitendra; Kodidala, Satyanath Reddy; Soni, Harsha; Singh, Priyanka; Sharma, Nirmal (Asian Journal of Medical Sciences, 2020)
Background: Newly admitted medical students experience a different curriculum, which can be a stressor and may be the reason of stress during student life. Stress may affect physiological, psychological and cognitive functions of the students. Aims and Objective: Aim of the study was to assess the effect of academic stress on physical activity level and cognitive functions in first year medical students. Materials and Methods: This observational study was conducted on 30 healthy newly admitted medical students (18 -25 years). The data was collected thrice, baseline, after two months and after four months. Stress was assessed by using DASS and Cohen perceived stress scale (PSS). GPAQ was used to estimate the physical activity level. And cognitive functions were assessed by using subjective method (MMSE questionnaire) and objective method (P300). Results: No significant difference of mean values of age, height, weight, BMI, physical activity level, DASS score, PSS and P300 latency were observed over the time to which recording was taken. The mean score of PAL represents the high physical activity. But the score of DASS and PSS represent severe and moderate stress level respectively. The significant difference was seen in the mean values of MMSE score and P300 amplitude over the time to which recording taken. Conclusion: The present study results we can conclude that students have stress during their academic period. And this stress might be helpful in potentiating the cognitive functions with the optimum physical activity.